Pro SharePoint Solution Development Combining .NET, SharePoint and Office 2007 - Hild, Ed; Adams, Susie (Apress : Imprint: Apress, 2007)
Pro SharePoint Solution Development: Combining .NET, SharePoint, and Office 2007 takes a practical problem/solution approach to common business challenges. You'll not only encounter interesting code samples, but also see how to combine these examples with the Microsoft collaboration platforms services. The books solutions focus on using Visual Studio Tools for Office to build the user interface layer. And solutions can interact with SharePoint as a service provider, taking advantage of SharePoints many collaboration features like document repositories, collaboration sites, and search functions. This book is unique because it starts with challenges that end users deal with every day when using the Microsoft collaboration platform to support business processes. The solutions are presented as the hypothetical business challenges of a fictional company. By presenting the examples in this context, authors Ed Hild and Susie Adams make it easier to relate to the challenges and solution value. And the goal of these examples is to build applications that apply the benefits of the Office desktop interface with the richness of SharePoints collaboration features.